The Social Status of the Disabled Individuals in Early Medieval Culmen in Poland - Matczak, Magdalena; Kozłowski, Tomasz; Chudziak, Wojciech (Archaeologia Historica Polona, 2025)
We investigated the social status of the disabled in early medieval Culmen in Poland, considering three scenarios. The first is that the disabled may have had a higher social status than the others because material wealth contributed to their survival and lengthened the progression of their ailments, whereas individuals from lower social status with similar afflictions would have died at earlier stages of their diseases. The second is that the disabled may have been neglected and devalued because of their ailments, thus causing them to be relegated to a lower social stratum. The third one might show that the social identity was made up of many different factors and the disabled might have had different social statuses. We analysed textual sources from the medieval period and examined 660 skeletons and 652 burials from Culmen using quantitative analyses. Textual analysis indicates that the cause of becoming disabled and initial social status played a crucial role in the perception of disabled individuals. Depending on these individuals with impairments were praised, cared for, left to beg, or rejected. Statistical analyses such as the χ2 test of independence, Mantel-Haenszel test for trend, and multiple correspondence analysis indicate that the disabled belonged to all higher social groups, not to the low one in Culmen. The outputs of our research show that the social identity was made up of many factors and the disabled might have had different social statuses.